Factors That Influence Turnover Intention Among Medical Employees of National Heart Institute Kuala Lumpur - Abd Latif, Mohamed (2011)
This study examines the differences related between four factors of job satisfaction which is pay, promotion, the job itself and supervision, and differences related between two demographic factor which is age and tenure (length of service) and turnover intention among medical employees of National Heart Institute Kuala Lumpur or Institut Jantung Negara (IJN). The study also determines the most dominant factor influence the turnover intention. The study hypothesized job satisfaction factors and demographic factors were having significant differences related with turnover intention. The methods used in the research to obtain data were via questionnaire. A total of two hundred and ten (210) medical employees of IJN were selected by modified systematic sampling as the sample of study. Data was analysed using ‘Statistical Package for Social Science’ (SPSS Window) Version 17. The tests involved were ANOVA, Pearson Correlation Coefficient, Factor Analysis and Multiple Regression. This study found that pay and supervision from job satisfaction factors were significantly related to turnover intention while promotion and job it-self were not significantly related. Both of demographic factors were not related to turnover. The research also found that the most dominant factor which influenced the turnover intention among IJN’s medical employee is pay.